Association between abnormal default mode network homogeneity and sleep disturbances in major depressive disorder - Ping Li; Feng Liu; Jingping Zhao; Muzhi Huang; Yangpan Ou; Huabing Li; Bing Lang; Wenbin Guo (General Psychiatry)
Background Sleep disturbance is a common comorbidity of major depressive disorder (MDD). However, network homogeneity (NH) changes of the default mode network (DMN) in MDD with sleep disturbances are unclear.Aims The purpose of this study was to probe the abnormal NH in the DMN in MDD with sleep disturbances and to reveal the differences between MDD with or without sleep disturbances.Methods Twenty-four patients with MDD and sleep disturbances (Pa_s), 33 patients with MDD without sleep disturbances (Pa_ns) and 32 healthy controls (HCs) were recruited in this study. Resting-state functional imaging data were analysed using NH.Results Compared with Pa_ns and HCs, Pa_s showed decreased NH in the left superior medial prefrontal cortex and increased NH in the right precuneus. There was a negative correlation between NH in the left superior medial prefrontal cortex and sleep disturbances (r=−0.42, p=0.001) as well as a positive correlation between NH in the right precuneus and sleep disturbances (r=0.41, p=0.002) in patients with MDD.Conclusions MDD with sleep disturbances is associated with abnormal NH in the DMN, which could differentiate pa_s from pa_ns. The DMN may play a crucial role in the neurobiological mechanisms of MDD with sleep disturbances.